MELAS with multiple stroke‐like episodes due to the variant m.13513G>A in MT‐ND5. Issue 2 (2nd February 2022) - Ghosh, Ritwik; Dubey, Souvik; Bhuin, Subhas; Lahiri, Durjoy; Ray, Biman Kanti; Finsterer, Josef
Abstract: Mitochondrial encephalopathy, lactic acidosis, and stroke‐like episodes (MELAS) is characterized by metabolic stroke, seizures, cognitive decline, lactic acidosis, ragged‐red fibers, headache, and vomiting, and in 80% of cases due to the mtDNA variant m.3243A>G. We report the case of a MELAS patient carrying a variant in subunit‐5 of the respiratory chain ( MT ‐ ND5 ), rarely reported in MELAS. The patient is a 33‐year‐old male, who experienced a series of stroke‐like episodes (StLEs) since age 23 years, which manifested clinically as seizures transient sensory disturbances, weakness, and visual or cognitive impairment. Over 9 years, these StLEs were misinterpreted as ischemic strokes, respectively, as cerebral vasculitis. He presented with mild, recurrent elevations of the creatine kinase. Initially, anti‐seizure drugs and steroids appeared to be beneficial. Despite good recovery of each single StLE, the patient experienced a progressive decline of cognitive functions and activities of daily living. Cerebral imaging showed corresponding stroke‐like lesions in changing locations. At age 32y, genetic work‐up revealed the variant m.13513G>A in MT ‐ ND5 . The patient profited significantly from a cocktail with anti‐oxidants/cofactors. This case shows that the variant m.13513G>A in MT ‐ ND5 can manifest as MELAS that StLEs recover spontaneously and that the course of MELAS is slowly progressive. Abstract : If MELAS does not coincide with the m.3243A>G variant, sequencing of the entire mtDNA is necessary to exclude other causes that are clinically or biochemically compatible with MELAS.